![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (7x - 11)3 = 25.52 + 200
=> (7x - 11)3 = 1000
=> (7x - 11)3 = 103
=> 7x - 11 = 10
=> 7x = 10 + 11
=> 7x = 21
=> x = 21 : 7
=> x = 3
b) x10 = 1x
=> x10 = 1
=> x10 = 110
=> x = 1
c) x10 = x
=> x10 - x = 0
=> x(x9 - 1) = 0
=> \(\orbr{\begin{cases}x=0\\x^9-1=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x^9=1\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
1/ 3(x - 2) = 9 => x - 2 = 3 => x = 5
2/ 3(x - 36) = 216 => x - 36 = 72 => x = 108
3/ (x - 3)3 = 33 => x - 3 = 3 => x = 6
4/ 2x = 32 => 2x = 25 => x = 5
5/ 3x - 16 = 2.74 : 73 = 14 => 3x = 30 => x = 10
6/ (6x - 39) : 3 = 201 => 6x - 39 = 603 => 6x = 642 => x = 107
7/ (3x - 15)2 = 81 => (3x - 15)2 = 92 => 3x - 15 = 9 => 3x = 24 => x = 8
8/ 3(x + 4) = 105 => x + 4 = 35 => x = 31
9/ 12x - 43 = 4.84 : 83 = 32 => 12x = 32 : 64 => 12x = 1/2 => x = 1/24
10/ 41 - (2x - 5) = 680 => 2x - 5 = -639 => 2x = -634 => x = - 317
![](https://rs.olm.vn/images/avt/0.png?1311)
1.
a) ( 57 + 59 ) . ( 68 + 610 ) . ( 24 - 42 )
= ( 57 + 59 ) . ( 68 + 610 ) . 0
= 0
b) 9 < 3x < 27
32 < 3x < 33
2 < x < 3
Vậy 2 < x < 3
2.
a) xy - 2x = 0
x ( y - 2 ) = 0
\(\Rightarrow\orbr{\begin{cases}x=0\\y-2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=3\\y=2\end{cases}}}\)
b) ( x- 4 ) . ( x - 3 ) = 0
\(\Rightarrow\orbr{\begin{cases}x-4=0\\x-3=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=4\\x=3\end{cases}}\)
c) Ta có : 3n+2 + 3n = 3n . 32 + 3n = 3n . ( 32 + 1 ) = 3n . 10 \(⋮\)10
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(2x+\frac{1}{7}=\frac{1}{3}\)
=> \(2x=\frac{1}{3}-\frac{1}{7}=\frac{7}{21}-\frac{3}{21}\)
=> \(2x=\frac{4}{21}\)
=> \(x=\frac{4}{21}:2=\frac{4}{21}.\frac{1}{2}=\frac{2}{21}\)
b/ \(3\left(x-\frac{1}{2}\right)=\frac{4}{9}\)
=> \(x-\frac{1}{2}=\frac{4}{9}:3=\frac{4}{9}.\frac{1}{3}\)
=> \(x-\frac{1}{2}=\frac{4}{27}\)
=> \(x=\frac{4}{27}+\frac{1}{2}=\frac{8}{54}+\frac{27}{54}=\frac{35}{54}\)
c/ \(\left(x-5\right)^2+4=68\)
=> \(\left(x-5\right)^2=68-4=64\)
=> \(\left[{}\begin{matrix}x-5=8\\x-5=-8\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}x=8+5=13\\x=-8+5=-3\end{matrix}\right.\)
d/ \(\left(\left|x\right|-\frac{1}{2}\right)\left(2x+\frac{3}{2}\right)=0\)
=> \(\left[{}\begin{matrix}\left|x\right|-\frac{1}{2}=0\\2x+\frac{3}{2}=0\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}\left|x\right|=0+\frac{1}{2}=\frac{1}{2}\\2x=0-\frac{3}{2}=-\frac{3}{2}\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}\left[{}\begin{matrix}x=\frac{1}{2}\\x=-\frac{1}{2}\end{matrix}\right.\\x=-\frac{3}{2}:2=-\frac{3}{2}.\frac{1}{2}=-\frac{3}{4}\end{matrix}\right.\)
e) \(5x+2=3x+8\)
=> \(5x-3x=8-2=6\)
=> \(2x=6\)
=> \(x=6:2=3\)
f/ \(26-\left(5-2x\right)=27\)
=> \(5-2x=26-27=-1\)
=> \(2x=5-\left(-1\right)=5+1=6\)
=> \(x=6:2=3\)
g/ \(\left(4x-8\right)-\left(2x-6\right)=4\)
=> \(4x-8-2x+6=4\)
=> \(\left(4x-2x\right)+\left(-8+6\right)=4\)
=> \(2x+-2=4\)
=> \(2x=4+2=6\)
=> \(x=6:2=3\)
h/ \(\left(x+3\right)^3:3-1=-10\)
=> \(\left(x+3\right)^3:3=-10+1=-9\)
=> \(\left(x+3\right)^3=-9.3=-27\)
=> \(x+3=-3\)
=> \(x=-3-3=-6\)
Ở đâu đấy !
\(\left(\frac{2x}{3}-3\right):\left(-10\right)=\frac{5}{3}\)
=> \(\frac{2x}{3}-3=\frac{5}{3}.\left(-10\right)\)
=> \(\frac{2x}{3}-3=-\frac{50}{3}\)
=> \(\frac{2x}{3}=-\frac{50}{3}+3\)
=> \(\frac{2x}{3}=-\frac{41}{3}\)
=> 2x = -41
=> x = -41/2